Different Multifractal Scaling of the 0 cm Average Ground Surface Temperature of Four Representative Weather Stations over China - Lei Jiang; Xia Zhao; Nana Li; Fei Li; Ziqi Guo (Advances in Meteorology)
The temporal scaling properties of the daily 0 cm average ground surface temperature (AGST) records obtained from four selected sites over China are investigated using multifractal detrended fluctuation analysis (MF-DFA) method. Results show that the AGST records at all four locations exhibit strong persistence features and different scaling behaviors. The differences of the generalized Hurst exponents are very different for the AGST series of each site reflecting the different scaling behaviors of the fluctuation. Furthermore, the strengths of multifractal spectrum are different for different weather stations and indicate that the multifractal behaviors vary from station to station over China.